Kampanye Tubuh Positif Perempuan “Real People Real Body” oleh @Nipplets_official - Visakha Ratna Dewi; Septia Winduwati (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2019)
The general public is introduced to an image of woman’s body that is slender, tall with a spotless sleek skin through fashion, advertisement and motion pictures which later become a standard of an ideal body. One of many options to straighten out this social issue is through the agency of a public relation activity known as Public Relation (PR) Campaign. Therefore, Nipplets, an online based lingerie company is fascinated to held a campaign about positive body via one of the most popular social media, Instagram. The purpose of this research is to gain extensive insight knowledges regarding the campaign itself, from the search stage all the way to the evaluation. The theoretical basis of this research are as follow; Communication, Persuasive communication, Social Media, ‘PR’ Campaign, Body Image and Cyber PR. This research uses a descriptive qualitative approach with a case study method. Based on the research outcome, it is believed that the lack of lingerie vendor who provide plus size lingerie in Indonesia and body insecurities have been the major motivations for @nipplets_official to carry out the Positive Body Campaign. The planning was involving numerous parties, including the production team, model, influencer and psychologist in order to deliver points of this campaign. The campaign is delivered through Instagram for approximately one month with Video marketing, Instagram Story and Photos which attired with words of wisdom as part of the strategy. The evaluation shows that the information is successfully delivered and can be utilized to complement the next campaign. Masyarakat diperkenalkan dengan citra dan standar tubuh perempuan yang langsing, tinggi, dan kulit yang halus nan bersih melalui fesyen, iklan, dan film. Salah satu cara untuk membantu menyelesaikan masalah sosial ini dengan lewat salah satu kegiatan public relations, yaitu kampanye PR. Maka dari itu Nipplets sebagai sebuah toko online yang menjual lingerie tertarik untuk mengadakan sebuah kampanye tubuh positif perempuan melalui media sosial Instagram. Penelitian ini bertujuan untuk mengetahui bagaimana kampanye Nipplets, mulai dari tahap research hingga evaluation. Landasan teori yang digunakan dalam penelitian ini antara lain; Komunikasi, Komunikasi Persuasif, Media Sosial, Kampanye PR, Body Image, dan Cyber PR. Penelitian ini menggunakan pendekatan kualitatif yang bersifat deskriptif dengan metode studi kasus. Hasil dari penelitian memperlihatkan kampanye tubuh positif yang dilakukan oleh @nipplets_official berlatarbelakangkan minimnya produsen lingerie untuk perempuan berukuran besar di Indonesia dan body insecurities. Perencanaan melibatkan berbagai pihak mulai dari production team, model, influencer, hingga psikolog untuk menyampaikan pesan dari kampanye ini. Kampanye ini dikomunikasikan melalui Instagram selama kurang lebih satu bulan dengan strategi video marketing, Instagram Story, dan unggahan foto bermuatan kata mutiara. Evaluasi yang didapat adalah pesan tersampaikan dengan baik dan menjadi masukan untuk kampanye berikutnya.